The MASCOT lander aboard Hayabusa2: The in-situ exploration of NEA (162173) Ryugu. (June 2021) - Ho, Tra-Mi; Jaumann, Ralf; Bibring, Jean-Pierre; Grott, Matthias; Glaßmeier, Karl-Heinz; Moussi, Aurelie; Krause, Christian; Auster, Ulrich; Baturkin, Volodymyr; Biele, Jens; Cordero, Federico; Cozzoni, Barbara; et al.
Abstract: After 3.5 years of cruise, and about 3 months in the vicinity of its target, the MASCOT lander was deployed successfully on October 3, 2018 by the Hayabusa2 spacecraft onto the C-type near-Earth asteroid (162173) Ryugu. After a free-fall of 5 ​min 51 ​s from an altitude of 41 ​m MASCOT experienced its first contact with the asteroid hitting a big boulder. The lander bounced for 11 ​min 3 ​s before it came to rest. MASCOT was able to perform science measurements with its payload suite at 3 different locations on the surface of Ryugu. It investigated the fine-scale structure, multispectral reflectance, thermal characteristics and magnetic properties. The surface consists of very rugged terrain littered with large surface boulders. The in-situ measurements confirmed the absence of fine particles and dust as already implied by the remote sensing instruments aboard the Hayabusa2 spacecraft. After about 17 ​h of operations, the MASCOT mission terminated with the last communication contact as its primary batteries depleted. This paper summarizes the MASCOT mission covering its four years of in-flight operations, its preparation for the descent, landing and in-situ investigation on the asteroid Ryugu until the end of its operation. Graphical abstract: Image 1